Prepričanja učencev, staršev in učiteljev o notranjih dejavnikih učne uspešnosti - Smrtnik Vitulić, Helena; Lesar, Irena (Revija za elementarno izobraževanje, 2014)
The Beliefs of Students, Parents and Teachers about Internal Factors of Academic Achievement. The main purpose of this paper was to determine the beliefs of students, teachers and parents about the internal factors of academic achievement and to verify whether their beliefs vary. In this paper the beliefs about the internal factors of academic achievement: personality traits, intellectual ability, language competence, interest in the subject and locus of control are thematised. The sample included 516 students from grades 5, 7 and 9 of 12 different basic schools in central Slovenia, 408 of their parents and 195 teachers. Amongst the broad range of personality traits in the survey questionnaire, parents selected openness and conscientiousness as the most important traits for academic success, while students selected openness and extroversion, and teachers selected agreeableness and emotional stability. In the opinion of the participants in the research, amongst other internal factors of academic success emphasised, those that have the greatest influence on academic achievement are interest in the subject and internal locus of control, while students’ intellectual ability and language competence are attributed slightly less importance. Beliefs regarding the individual factors of academic achievement vary between the groups of participants. In the future, it would be sensible to encourage students, teachers and parents to reflect on the meaning of the individual factors of academic achievement, and especially to speak with them about the factors on which each respective group can exert an influence in order to improve students’ academic achievement.
Keywords: beliefs; academic achievement; internal factors; students; parents; teachers